2018
DOI: 10.1123/jpah.2016-0676
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Physical Activity and Screen Time Among Brazilian Children

Abstract: Our results showed an association between low PA levels and high amount of screen time among children and adolescents, showing that is necessary to encourage an active lifestyle, decreasing time spent on television, computers, cell phones, and video games.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 10 publications
4
18
0
2
Order By: Relevance
“…We can hypothesize that participation in organized and unorganized PA leads to an increase in overall PA, which results in compensatory changes in the remaining movement behaviors. Previous studies support this assumption by showing that a greater amount of time spent engaged in PA is associated with lower ST and longer sleep duration [46,47]. Furthermore, we found that fruit and vegetable intake, parental characteristics, and sleep efficiency were also associated with specific combinations of recommendations.…”
Section: Discussionsupporting
confidence: 80%
“…We can hypothesize that participation in organized and unorganized PA leads to an increase in overall PA, which results in compensatory changes in the remaining movement behaviors. Previous studies support this assumption by showing that a greater amount of time spent engaged in PA is associated with lower ST and longer sleep duration [46,47]. Furthermore, we found that fruit and vegetable intake, parental characteristics, and sleep efficiency were also associated with specific combinations of recommendations.…”
Section: Discussionsupporting
confidence: 80%
“…We can hypothesize that participation in organized and unorganized PA leads to an increase in overall PA, which results in compensatory changes in the remaining movement behaviors. Previous studies support this assumption by showing that a greater amount of time spent engaged in PA is associated with lower ST and longer sleep duration [49,50]. Furthermore, we found that fruit and vegetable intake, parental characteristics, and sleep e ciency were also associated with speci c combinations of recommendations.…”
Section: Discussionsupporting
confidence: 79%
“…We can hypothesize that participation in organized and unorganized PA leads to an increase in overall PA, which results in compensatory changes in the remaining movement behaviors. Previous studies support this assumption by showing that a greater amount of time spent engaged in PA is associated with lower ST and longer sleep duration [46,47].…”
Section: Discussionmentioning
confidence: 87%